Prepulse inhibition and P50 suppression: Commonalities and dissociations - Oranje, Bob; Geyer, Mark A.; Bocker, Koen B.E.; Leon Kenemans, J.; Verbaten, Marinus N. (Psychiatry research, 2006)
Patients with schizophrenia exhibit reduced levels of both prepulse inhibition of the startle reflex (PPI) and condition-test suppression of the P50 event-related potential. This study investigated the extent to which PPI and P50 suppression, which exhibit similar parametric sensitivities, are intrinsically auditory phenomena or can be induced cross-modally, and reflect common or distinct neural mechanisms of inhibition. PPI, N100, and P50 were assessed in 20 healthy male volunteers, using auditory test probes and both visual and auditory lead stimuli, separated by 100- or 500-ms interstimulus intervals (ISIs). PPI was found in the auditory-lead condition across the complete group, and with visual-lead stimuli in approximately half of the subjects. Intra-modal auditory PPI was significantly higher with the 100-ms ISI than with the 500-ms ISI. P50 suppression was found only with the 500-ms ISI, with no difference between the auditory and visual conditions. Source analyses revealed that suppression was associated with frontal cortical activity. N100 suppression was found only in the auditory condition, with no difference between 100- and 500-ms ISIs. Although both phenomena are considered to provide operational measures of gating, PPI and P50 suppression are differentially sensitive to ISI and therefore reflect partly different neural mechanisms. They are not intrinsically auditory phenomena, and both appear to involve frontal cortical activity. In contrast, N100 suppression is most likely based on refractory mechanisms intrinsic to the auditory system.